Assessing the Preparedness of Islamic Religious Education Teachers in Indonesia for Technology-Based Learning Innovations - Yarun, Ayuningtias; Abu Bakar, M Yunus; Kholis, Nur (TA'DIBUNA: Jurnal Pendidikan Agama Islam, 2023)
Media technology-based learning innovations in Islamic education are currently a fascinating area of study. Digital media-based learning has been implemented in Islamic education. However, the reality is that there are still teachers who have not embraced technological media in their teaching practices. This study aims to determine the level of preparedness among Islamic education teachers to innovate in learning by utilizing technology as a tool for developing teaching materials, as well as to identify the obstacles preventing teachers from utilizing it. The research method employed is descriptive qualitative research to process the required information data. The research findings indicate that (1) Islamic education teachers have implemented learning innovations through technological media, recognizing the challenges faced in Islamic education that stem from the need to constantly update students' knowledge. (2) Islamic education teachers consciously make efforts to incorporate technological media in developing teaching materials, enabling them to cater to students' preferred learning styles. (3) Islamic education teachers are ready to undertake innovations in teaching material development. They view technology as an effective tool, recognizing that without it, Islamic education lessons may lag behind and lack appeal. This research is valuable in addressing the concerns of Islamic education teachers, as it highlights the importance of integrating technological media in Islamic Education learning, which has a positive impact and greatly enhances the teaching and learning process.